Treatment of temporomandibular disorder using occlusal splint - Agus Dahlan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Patient suffering from occlusal abnormality is usually detected months or even years when the acute patient visits a dentist, and generally the patient does not receive direct treatment upon his complaints since minimum information is available on this type of treatment. In general, the dentist provides medication only or conducts incorrect selective grinding where in fact, the patient does not feel better from the previous conditions. Purpose: The objective of this study is to discuss the treatment on the dysfunctional temporomandibular joint followed by orofacial pain caused by occlusal disorder using occlusal splint. Case: In this case, a forty three years old male having trouble with the joint on the left jaw followed by orofacial pain caused by occlusal disorder. Case Management: Initial treatment with occlusal splint makes the patient comfortable and recovers from his complaints since the patient could restructure the chewing muscles. This treatment will be more successful if the dentist has the knowledge to use and choose occlusal splint method properly. Occlusal Splint could be used as a supporting therapy and consideration as one of the therapies to avoid the unwanted side effects. The use of occlusal splint is meant as an alternative of the main therapy in overcoming the problem of occlusal splint. Conclusion: Finally, therapy with occlusal splint is very effective as an alternative treatment to handle the dysfunction of temporomandibular joint caused by occlusion.